Antonio de Sampaio Doria e a modernização do ensino em São Paulo nas primeiras décadas do século XX - Medeiros, Valeria Antonia (2005)
This paper deals with the reconstitution of Antonio de Sampaio Dória´s intellectual and professional trajectory in the 1910s through the 1930s, in São Paulo. Undergraduated by the Law School of São Paulo, he joined the Escola Normal da Praça in 1914, taking the chair of Psychology, Pedagogy and Civic Education. He engaged in networks of social relations in which he participated as a founder and member of the steering group, such as: the Nationalist League, the Society of Education and the National Lyceum of Rio Branco. By means of such social networking Sampaio Dória cooperated, as a producer and promoter, to construct a project of nation, in which the educational causes had an outstanding place. Acknowledged by his contemporaries as one of the major leaders of the cultural elite in the state of São Paulo, he was invited to take the position of director-general of the Public Instruction in the state, in 1920, the moment whe he organized the first school census, and also he submitted the project to reform the public instruction, which is considered in the education historiography as landmark of the movements that modernized school teaching at the time. Although he stayed at this position for a brief period, it is the moment of highest public expression of Sampaio Dória, which proved to be the event that represented a network of relations which molded the education in the state of São Paulo in the subsequent decades